2015
DOI: 10.3892/ol.2015.3944
|View full text |Cite
|
Sign up to set email alerts
|

Villoglandular papillary adenocarcinoma of the uterine cervix: A report of 4 cases and a review of the literature

Abstract: Abstract. To investigate the clinicopathological features, management and prognosis of villoglandular papillary adenocarcinoma (VGPA) of the uterine cervix, the current study presents 4 cases of VGPA of the uterine cervix. The median age of the patients was 55 years (range, 47-70 years), with all 4 patients presenting with stage Ib disease. Human papillomavirus (HPV) infection was detected in 3 patients; this was mainly HPV-16. No history of oral contraceptive use was found in these cases. While 2 of the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…On gross examination, the tumours are mostly polypoidal or papillary neoplasms as seen in our case although occasionally they can present as infiltrative and friable lesions. 4 The three important histopathological features of VGPA are: an exophytic growth pattern; papillary architecture and mild to moderate nuclear atypia, all of which were seen in present case. 2 On microscopic examination, each papilla in the villoglandular structure, has a central pedicle that ranges in size and shape from short and thick to long and slender.…”
Section: Figure 1 Photomicrograph Of the Tumour Showing Long And Slesupporting
confidence: 61%
“…On gross examination, the tumours are mostly polypoidal or papillary neoplasms as seen in our case although occasionally they can present as infiltrative and friable lesions. 4 The three important histopathological features of VGPA are: an exophytic growth pattern; papillary architecture and mild to moderate nuclear atypia, all of which were seen in present case. 2 On microscopic examination, each papilla in the villoglandular structure, has a central pedicle that ranges in size and shape from short and thick to long and slender.…”
Section: Figure 1 Photomicrograph Of the Tumour Showing Long And Slesupporting
confidence: 61%
“…The etiology of VGA is still obscure. HPV infection, particularly high-risk types, in the role of molecular pathogenesis of VGA has been put forward, 12 and high-risk types HPV were indeed detected in 3 of our 4 patients. In 1993, Jones et al 6 proposed a possible relationship between VGA and oral contraceptives (OC) usage.…”
Section: Discussionmentioning
confidence: 64%
“…Previously, oral contraceptive use was linked to the development of VGA [ 6 ]. Yet, recent studies have not demonstrated a significant relationship between oral contraceptive use and VGA development [ 7 ]. Conversely, HPV infection, particularly high-risk HPV, is considered a risk factor for VGA development [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, recent studies have not demonstrated a significant relationship between oral contraceptive use and VGA development [ 7 ]. Conversely, HPV infection, particularly high-risk HPV, is considered a risk factor for VGA development [ 7 ]. A recent study suggests a potential influence of estrogen on carcinogenesis in cervical adenocarcinoma cases with high-risk HPV infection [ 8 ].…”
Section: Discussionmentioning
confidence: 99%